RELIGION AND COMEDY: EXAMINING ISLAM IN PRISKA BARU SEGU AND BORIS BOKIR'S STAND-UP COMEDY - Abraham Zakky Zulhazmi; Syafawi Ahmad Qadzafi; Virdika Rizky Utama (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
In Indonesia, stand-up comedy performances have become popular in recent years. Stand-up comedy performances are completed and broadcast regularly on Indonesian television, and easily be found on social media such as YouTube. However, some stand-up comedy material is considered offensive and has resulted in legal cases. This includes materials that carry religious themes. This research analyzes the representation of Islam in the stand-up comedy material of Priska Baru Segu and Boris Bokir on Deddy Corbuzier's YouTube channel. This study is descriptive qualitative research. The stand-up comedy material of Priska Baru Segu and Boris Bokir is examined using critical discourse analysis by Teun A. van Dijk. This research concludes that the representation of Islam in the stand-up comedy material of Priska Baru Segu and Boris Bokir depicts Islam as hegemonic. This image emerges in the relationship between the majority group (Islam) and minorities in Indonesia. The strengthening of majoritarianism further solidifies the hegemony and dominance of Islam. Priska and Boris present material that represents religious issues in Indonesia: the closure of churches, the pros and cons of saying Merry Christmas, raids on restaurants during Ramadan, and issues of identity politics. Comedy based on religious material that Priska and Boris deliver operates under the shadow of societal sensitivities and accusations of blasphemy.